2004
DOI: 10.1353/hpu.2004.0061
|View full text |Cite
|
Sign up to set email alerts
|

How do Urban African Americans and Latinos View the Influence of Diet on Hypertension?

Abstract: Uncontrolled hypertension and its complications continue to be major health problems that disproportionately affect poor minority communities. Although dietary modification is an effective treatment for hypertension, it is not clear how hypertensive minority patients view diet as part of their treatment, and what barriers affect their abilities to eat healthy diets. We conducted nine focus groups with 88 African American and Latino patients treated for hypertension to assess their knowledge, attitudes, behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
4
47
1
4
Order By: Relevance
“…Our findings support results from other studies and concur that interventions for prevention need to be developed with input directly from affected population groups 7,[9][10][11]17 . Participants of this study stated that they would benefit from ongoing interactive discussion groups to gain management skills, education, and support for their conditions, which would increase awareness about diabetes and hypertension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings support results from other studies and concur that interventions for prevention need to be developed with input directly from affected population groups 7,[9][10][11]17 . Participants of this study stated that they would benefit from ongoing interactive discussion groups to gain management skills, education, and support for their conditions, which would increase awareness about diabetes and hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Burns et al conducted interviews with diabetic study participants and found that an effort to eat right was a daily challenge and that the cost and availability of desired foods hindered appropriate self-management. 7 Cost is not only higher for healthier foods, but frequently healthier foods are absent from grocery stores in lower socioeconomic neighborhoods 7,9,13,17 . Among our study population, one major barrier expressed by participants was difficulty breaking the habit of eating unhealthy foods that are commonly found within their community and in traditional ethnic foods.…”
Section: Discussionmentioning
confidence: 99%
“…At the very least, published materials should be understandable to readers, free of medical jargon (or provide meanings of terms), and presented in languages other than English; of numerous booklets published by the National Diabetes Information Clearinghouse (NDIC), only four are available in Spanish "to help educators and patients improve diabetes management" (concerning what, when, and how much to eat plus information about medications), and none has been translated to other languages. Documents and ads "targeted" at or "tailored" for a particular racial or ethnic audience (Kreuter et al 2002) should include images of people from that group; recipes must take into account not only familiar ingredients but also the flavor principle associated with different cuisines (Rozin 1983); workshops on nutrition should be held at churches, botánicas, and other community centers where people feel comfortable, rather than exclusively at clinics; and dieticians ought to provide food preparation demonstrations and lead tours to grocery stores to apply dietary recommendations (for these and several other suggestions below, see Brown et al 2002;James 2004;Horowitz et al 2004;Liburd 2003;and Tripp-Reimer et al 2001).…”
Section: -Peter Singer Animal Liberationmentioning
confidence: 99%
“…5 Depression and emotional barriers for disease treatment and program participation have been mentioned in previous qualitative studies as well. 8,18,27,31 Addressing emotional well-being in CVD-prevention programs may improve attendance.…”
Section: Discussionmentioning
confidence: 99%